Analisis Kesalahan Berbahasa dalam Keterampilan Menulis Siswa Nida Suksasat School Thailand: Analysis of Language Errors in Writing Skills of Nida Suksasat School Thailand Students - Putri, Dilla Eka; Sitepu, Tepu (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Writing skills are one of the important competencies in learning Indonesian as a foreign language, especially in international school environments such as Nida Suksasat School, Thailand. This study aims to analyse language errors in grade X students' writing and identify the factors that cause these errors. This study uses a descriptive qualitative approach with data collection techniques through documentation of student writing results, interviews with subject teachers, and observations of learning activities in the classroom. Data were analysed by classifying errors based on linguistic aspects, namely phonology, morphology, syntax, and semantics. The study results showed that the most common errors were related to spelling, sentence structure, and improper punctuation. In addition, errors were found in word choice and paragraph arrangement that were less coherent, thus disrupting the logical flow of the writing. The factors that cause these errors include interference from the mother tongue (Thai), limited mastery of Indonesian vocabulary, and minimal structured writing practice in class. The lack of interactive learning media, varied learning resources, and a less contextual teaching approach also contributes to students' low writing skills. Based on these findings, the researcher recommends strengthening the learning of language basics through directed writing exercises and applying teaching strategies that are more communicative, contextual, and appropriate to the background of foreign students. In conclusion, systematic, sustainable, and student-needs-based pedagogical interventions are needed to improve writing skills in international schools' learning of Indonesian as a foreign language.